Islamic Theologians and the Different Genres of I‘jāz: A Case Study of Rummāni & Khaṭṭābi - Junaid Akbar; Bacha, Sayyed Abul Salam (Journal of Islamic and Religious Studies, 2017)
There are several points which illustrate Qur’ānic I‘jāz and probably rely on Islamic Theologians -Mutakallimin’s- efforts as well as exertions regarding Qur’ānic I‘jāz. Mutakallimin for having good command over Arabic rhetorical structures have demonstrated Qur’ānic I‘jāz in two contexts: theoretically and empirically. They actually validated, that Qur’ān is the book of Allah Almighty, through comparing both standard Arabic texts: prose and poetry into face of Qur’ānic text. All these cherished efforts of Mutakallimin are rooted in Arabic rhetoric which stands for that Arabic Rhetoric and ‘ilm al-Kalām; both have very primary relation resulting in that cannot be ignored while analyzing I‘jāz phenomenon.